Reimagining a Buddhist Cosmopolis: Conveying Marble Buddhas from Burma to China, 1890s-1930s - Beiyin Deng (Journal of Global Buddhism, 2023)
Discussions about Buddhist connections between China and Southeast Asia in the late Qing and Republican periods often conform to a meta-narrative of Buddhist modernism that emphasizes the trajectories of eminent monks and reformative initiatives in and beyond China. Drawing on research on archives in China and Myanmar (Burma) and field visits to temples and museums in China, this article investigates the efforts to convey marble Buddhas from Burma to China by a broad spectrum of Chinese Buddhists from the 1890s to 1930s as a strain of Buddhist mobility that has receive scant attention in the studies of transregional Buddhist interconnectivities. It examines how the fascination with marble, which is vernacularly categorized as jade/white jade in Chinese, motivated such endeavors and how these icons shaped the perception of a developing Buddhist cosmopolis among Chinese Buddhists by helping them locate Burma in the Buddhist world in a spiritually and materially meaningful way.